1998
DOI: 10.1016/s0735-1097(98)00374-x
|View full text |Cite
|
Sign up to set email alerts
|

Coupled systolic-ventricular and vascular stiffening with age

Abstract: Arterial stiffening with age is matched by ventricular systolic stiffening even without hypertrophy. The two effects contribute to elevating systolic pressure sensitivity to altered chamber filling. In addition to recognized baroreflex and autonomic dysfunction with age, combined stiffening could further enhance pressure lability with diuretics and postural shifts in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
90
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 399 publications
(98 citation statements)
references
References 38 publications
5
90
1
2
Order By: Relevance
“…The interaction of ventricular and arterial properties, or coupling, is an important and largely under-appreciated determinant of cardiac performance (1)(2)(3)9). Because cardiac reserve during maximal exertion decreases with increasing age in healthy humans (5), evaluation of rest and exercise ventricular-vascular coupling in a large, healthy cohort illuminates reasons for this decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of ventricular and arterial properties, or coupling, is an important and largely under-appreciated determinant of cardiac performance (1)(2)(3)9). Because cardiac reserve during maximal exertion decreases with increasing age in healthy humans (5), evaluation of rest and exercise ventricular-vascular coupling in a large, healthy cohort illuminates reasons for this decline.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, EF is determined by the interaction of arterial and ventricular properties (1)(2)(3). Effective arterial elastance (EaI) is a steady-state arterial parameter that characterizes the functional properties of the arterial system by incorporating peripheral vascular resistance, total lumped vascular compliance, characteristic impedance, and systolic and diastolic time intervals (1).…”
mentioning
confidence: 99%
“…These changes occur concomitantly with a late augmentation index (AGI) of the carotid pressure pulse. An increase in arterial stiffness increases the vascular load on the heart, resulting in adverse changes in left ventricular (LV) structure and function (4), in part, by altering coupling efficiency between the vasculature and the heart (5). Epidemiologic studies in humans have shown that elevated measures of arterial stiffness are reliable predictors of cardiovascular morbidity and mortality (6).…”
mentioning
confidence: 99%
“…First, a smaller body height has been associated with early return of reflected waves to the central aorta in systole rather than diastole (54), which causes a decrease in pulse wave amplification, exemplified by an increase in pulse pressure (55). Further attenuation in pulse pressure amplification has also been shown in postmenopausal women (12,56).…”
Section: Discussionmentioning
confidence: 99%